Gambaran Psychologycal Wellbeing Pada Pasien Stroke Di RSUD dr. Rm. Djoelham Binjai - Evarina Sembiring; Amila; Simamora, Marthalena (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
Stroke can affect the sufferer's life, including physically, emotionally, psychologically, cognitively and socially. The physical and psychological problems of stroke sufferers are factors that cause disruption to quality of life. Psychological well-being or psychological well-being is a condition where a person can accept one's own strengths and weaknesses as well as satisfaction from a psychological perspective. The aim of this study was to identify a clearer picture of the psychological well-being of stroke patients treated at RSUD Dr. RM Djoelham, Binjai City. This research is a descriptive study using a cross sectional approach. The respondents for this study were 40 patients, the sampling technique used was purposive sampling. Data collection uses a questionnaire or questionnaire. The statistical test used is frequency distribution. Psychological well-being was high at 72.5%. It is recommended that further research be conducted regarding factors that can influence psychological well-being in stroke patients.